Activated charcoal significantly reduces the amount of colchicine released from Gloriosa superba in simulated gastric and intestinal media. (14th September 2017) - Zawahir, Shukry; Gawarammana, Indika; Dargan, Paul I.; Abdulghni, Mahfoudh; Dawson, Andrew H.
Abstract: Background: Poisoning with Gloriosa superba, a plant containing colchicine, is common in Sri Lanka. Objectives: This study was to estimate release of colchicine from 5 g of different parts of Gloriosa superba in simulated gastric and intestinal media, and examine the binding efficacy of activated charcoal (AC) to colchicine within this model. Methods: A USP dissolution apparatus-II was used to prepare samples for analysis of colchicine using HPLC. Results: Cumulative colchicine release from tuber in gastric media at 120 minutes was significantly higher (2883 μg/g) than in intestinal media (1015 μg/g) ( p < .001). Mean ± SD cumulative colchicine concentration over 2 hours from tuber, leaves and trunk in gastric medium was 2883.15 ± 1295.63, 578.25 ± 366.26 and 345.60 ± 200.08 μg/g respectively and the release in intestinal media was 1014.75 ± 268.16, 347.40 ± 262.61 and 251.55 ± 285.72 μg/g respectively. Introduction of 50 g of AC into both media made colchicine undetectable (<0.1 μg/ml). Conclusions: The tuber released the highest quantity of colchicine. The colchicine release and elapse time to achieve saturated, equilibrium dissolution mainly depends on physicochemical properties of plant part. Significant in vitro binding of colchicine to AC suggests that AC has a role in decontamination of patients presenting to hospital after ingestion of Gloriosa superba .